Implementing Aproiri Algorithm for Predicting Result Analysis - Nurul A., Emran; Aziz, A. A.; Jusoh, J. A; Idris, W. M. R. W.; Hassan, H. (2013)
University or Higher Learning Institution is a platform to train students in specific domain area that will become an asset for a country. One of the critical issues in University is to avoid dropout students. Educational Data Mining (EDM) is an emergent discipline in developing methods to explore the unique types of data from the educational context. One of the techniques applied in EDM is an Association Rules (AR) which is to find a pattern of one element influencing other element. In this paper, AR technique has been utilized to predict students’ results based on a group of the previous students results. Clustering method has been used to classify the specific subject category. Finally, a system known as Result Prediction System (REPS) has been developed to perform automatically the AR analysis on the academic data using PHP and MYSQL databases.